CARA PENGGUNAAN APLIKASI LINKTREE GRATIS DENGAN MUDAH - Samriana; Saputri, Andi Aprilia (Sindoro: Cendikia Pendidikan, 2024)
Linktree is an application that allows users to create personalized and customizable pages, which can host multiple links related to the subject matter. Linktree can help teachers to organize and share information related to subject matter more quickly and efficiently. The purpose of using Linktree is to allow users to collect and organize multiple links into one page that is easy to personalize and design. The type of research conducted is qualitative descriptive research, which collects in-depth data on various aspects related to how to use the linktree application for free easily. By using Linktree, users can easily organize and share information related to business or subject matter, thus facilitating the learning and teaching process.